AIDS and injecting drug use: very risky behaviour in a Perth sample of injecting drug users - Loxley, Wendy; Hawks, D. (Taylor and Francis, 1994)
This research was carried out in 1990 to examine high-risk injecting and sexual behaviour in a sample of injecting drug users (IDUs) in Perth. The study was a cross-sectional survey with a convenience sample drawn from drug treatment (54%) and non-treatment (46%) populations. In the sample of 150 IDUs, there were 11 very risky drug behaviour (VRDB) and 63 very risky sex behaviour (VRSB) respondents. Four respondents fell into both categories. Independent comparisons were made between each risk group and the rest of the sample. The VRDB respondents were heterosexual men, most of whom were in long-term monogamous relationshiys, with heavier levels of drug use than the rest of the sample. The VRSB respondents were largely single and mainly heterosexual, with more sexualpartners than the rest of the sample. It was concluded that there was little evidence that very risky behaviour was related to a general risk-taking dimension, to inadequate knowledge about AIDS or to a low assessment of personal vulnerability to AIDS. However, situational influences in association with heavy drug use appeared to be a major component of high-risk injecting behaviour, while high-risk sexual behaviour appeared more to be a reflection of community norms about heterosexual sexual behaviour. The study should be replicated with larger samples, particularly as the VRDB group was so small, but if the findings are reproduced in other studies, it suggests that serious attention should be paid to the promotion of safer sex among injecting drug users.